Psychoanalytic Conversations with States of Spirit Possession: Beauty in Brokenness - Masih, Shalini (Lexington Books, 2023)
Shalini Masih grew up in a stimulating environment of priests and healers, witnessing firsthand states of spirit possession and exorcism. In adulthood, she revisited these experiences, motivating her to extend psychoanalysis outside the clinic's realms into spaces of traditional healing. The outcome of her detailed exploration acknowledges the hugely productive interface between cultural manifestations and concerns of psychoanalysis without reducing the phenomenon of spirit possession to something formulaic. Instead, Psychoanalytic Conversations with States of Spirit Possession: Beauty in Brokenness highlights the intrinsic beauty of this complex experience, illustrating relevant themes through culturally sensitive psychoanalytic conversations with participants who felt haunted and possessed by ghosts. The author's journey reveals the ghosts of her own inner world. She draws upon her reveries, dreams, and nightmares to make sense of the unconscious processes in her informant's testimonies, journeys that are so often undertaken from one grotesque ghost to another until these ghastly beings reappear as broken part-selves in search of the glue of spiritual meaning.